Effect of Rewards on Employee Performance At PT Sejahtera Mandiri Lubuk Pakam - Windari, Ayu; John F. Marpaung (SEAN Institute, 2022)
Sejahtera Mandiri Lubuk Pakam as many as 32 people. The results of this study indicate that the independent variable, namely Reward (X), has a positive and significant effect on the dependent variable, namely Employee Performance (Y) at PT. Sejahtera Mandiri Lubuk Pakam.